Pocket therapy for emotional balance : quick DBT skills to manage intense emotions - McKay, Matthew; Wood, Jeffrey C.; Brantley, Jeffrey (New harbinger publications pocket therapy, 2020)
"In Pocket Therapy for Emotional Balance, three clinical psychologists and authors of The Dialectical Behavior Therapy Skills Workbook offer quick, evidence based tips and tools for managing intense emotions in the moment. Using this handy, take-anywhere guide, readers will find freedom from overwhelming thoughts and feelings, find a sense of calm, and live a more balanced life"--